The effect of water molecules on paraquat salts: from physicochemical properties to environmental impact in the Brazilian Cerrado - Aguiar, Antônio S. N.; Costa, Luiz B.; Borges, Igor D.; Aguirre, Gerardo; Tejerina-Garro, Francisco L.; Dutra e Silva, Sandro; Napolitano, Hamilton B. (Frontiers in Chemistry, 2023)
Introduction: The green revolution model that is followed in the Brazilian Cerrado is dependent on mechanization, chemical fertilization for soil dressing and correction, and the use of herbicides. Paraquat is a methyl viologen herbicide marketed as bipyridylium dichloride salts and used (in low doses) to combat weeds in their post-emergence stage. It is a non-selective pesticide that causes the peroxidation of the lipids that make up the cell membrane, and when it comes into contact with foliage, it results in the death of the plant. Methods: The effect of water molecules co-crystallized in Paraquat salt structures was analyzed in anhydrous, dihydrate, and trihydrate forms to understand those physicochemical properties in its redox activity. The frontier molecular orbitals were also carried out using DFT to obtain the chemical reactivity of the bipyridylium cation. Finally, the supramolecular arrangements were evaluated to analyze the physicochemical stability and acquire insights on superoxide anions. Results and discussion: The electronic structure indicated that the BP cation presents an acidic character due to its low ELUMO value, while the salt has a more basic character due to its high EHOMO value. For this reason, the BP ion is more susceptible to reduction during the weeds’ photosynthesis process. During the process of plant photosynthesis, PQ is reduced to form a stable radical cation. In the supramolecular arrangement, the presence of water molecules increases the number of strong H-bonds, while the weak/moderate H-bonds are stabilized. PQ’s toxic effects are observed in wildlife, domesticated animals, human populations, and ecosystems. The influence of PQ on the terrestrial environment is limited because of the soil adsorption capacity associated with good agricultural practices. The current use of good agricultural practices in the Cerrado seems not to prevent the environmental impacts of herbicides like PQ because it aims for the expansion and profitability of large-scale farming based on input-intensive practices instead of sustainable agriculture processes.